Eco-friendly management of rice stem borer in spring rice (chaite-5) - Pranita Kakshapati; Raksha Shrestha; Sumira Khatiwada (Future Science, 2022)
Since chemical pesticides have a variety of short- and long-term social, economic, and environmental repercussions, research was conducted in Baniyani, Jhapa, Nepal from January to July 2021 to manage the Yellow Stem Borer (YSB) of rice in an environmentally responsible manner. The research followed the Randomized Complete Block Design (RCBD) with three replications and seven treatments using the spring rice variety Chaite-2. The seven treatments used were spinosad 45% SC, Bacillus Thuringensis var krustaki + saccharopolyspora spinosad 15% SC, Azadiractin 0.3%, Chinaberry (Bakaino) leaf extract, Mugwort (Titepati) leaf extract, Metarhizium anisopliae and untreated plot. In order to evaluate the efficacy of the treatments, the number of dead heart and white head symptoms were counted at various time intervals, namely 7, 15, and 21 days after spraying (DAS). At the vegetative and reproductive stages of rice, the rice stem borer causes the symptoms known as